Eczema herpeticum and impetigo herpetiformis, is there a link? - Fortunato Cassalia; Jacopo Tartaglia; Davide Zardo; Francesca Caroppo; Anna Belloni Fortina (Wiley, 2023)
Abstract Impetigo herpetiformis (IH) is a rare variant of pustular psoriasis with typical onset during the third trimester of pregnancy; it is characterized by erythematous plaques lined with sterile pustules and sometimes there may be systemic involvement. On the other hand, eczema herpeticum (EH) is defined as a disseminated skin infection by herpes simplex virus type 1, which mainly affects patients characterized by an impaired integrity of the skin barrier, mostly atopic dermatitis. We report the case of a 30‐year‐old woman, primigravida at 28 + 3 weeks of gestation, who after asymptomatic severe acute respiratory syndrome coronavirus 2 infection for about 7 days presented to the emergency room with a burning and itching rash on the trunk and limbs. She reported a long‐standing history of atopic dermatitis and recurrent herpetic eruptions. The diagnosis of EH was made and systemic therapy was set with excellent results. A few days later, the patient developed a pustular rash in the areas previously affected by EH, with histologic features of IH. A relation between EH and IH is thus suggested.